2020
DOI: 10.2147/ccide.s261308
|View full text |Cite
|
Sign up to set email alerts
|

<p>Peripheral Adenomatoid Odontogenic Tumor — A Rare Cause of Gingival Enlargement: A Case Report with CBCT Findings</p>

Abstract: Introduction: Adenomatoid odontogenic tumor (AOT) is an uncommon benign odontogenic lesion with varied clinical and histological presentation. It has slow growth potential and a low recurrence rate. The tumor is mainly seen in females in the second decade of life, predominantly affecting the maxilla and associated most often with unerupted canine teeth, earning the epithet "two-thirds tumor". There are three variants: intrafollicular, extrafollicular, and peripheral. The peripheral or extra osseous type is a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 28 publications
2
12
2
Order By: Relevance
“…As mentioned by Câmara et al 20 , 77% of AOT cases are initially identified as a dentigerous cyst. In agreement with Sadasivan et al 10 , the clinical and radiographic diagnosis become inconclusive, requiring the histopathological examination for diagnostic elucidation.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…As mentioned by Câmara et al 20 , 77% of AOT cases are initially identified as a dentigerous cyst. In agreement with Sadasivan et al 10 , the clinical and radiographic diagnosis become inconclusive, requiring the histopathological examination for diagnostic elucidation.…”
Section: Discussionsupporting
confidence: 81%
“…Liu et al 14 argues that this pathology is asymptomatic, of slow growth, painless and that rarely exceeds 3 cm in the higher diameter 6,10 . Genno et al 4 adds that AOT discovery usually occurs in routine examinations when investigating the absence of a tooth 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, CBCT provides a better display of the extent and the complex spatial relationship of the lesions with the surrounding structures. 21,22 The diagnosis suspected based on clinical and radiographic data can only be confirmed by the anatomopathological study of the operative pieces.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CBCT provides a better display of the extent and the complex spatial relationship of the lesions with the surrounding structures. 21 , 22 …”
Section: Discussionmentioning
confidence: 99%